INFORMATION TECHNOLOGIES IN THE PROCESS OF TRAINING MARITIME SPECIALISTS - Lyashenko У.І. (Journal of Information Technologies in Education (ITE), 2015)
The article represents main questions concerning usage of the newest informationcommunicative technologies of maritime educational establishments in the process of training specialists of corresponding specialities; reviews the problem of training cadets of Maritime educational institutions by means of information technologies while studying professionally focused disciplines; means of implementation information technologies into the educational process and their practical usage in future professional activity on board a ship are disclosed; the importance of online communications in teaching foreign language speaking, listening comprehension, writing and test tasks implementation to control forming of cadet’s lexical, phonetic and grammar skills areproved; presentations of authentic professionally oriented materials from the newest electronic sources on lectures on disciplines «Marine diesel installations», «Power management system»,«Radio-navigational devices and systems». The author of the article grounds practicability of implementation of the newest information communicative technologies into educational process in classroom and extracurricular work,cadets are given an opportunity to get authentic professionally focused information on professional discipline, to extend knowledge on these disciplines and to realize control of formation corresponding competences.